Response to Hydralazine-Valproate in a Patient with Mycosis Fungoides - Alfonso Dueñas-Gonzalez; Maria Teresa Vega; Déborah Martinez-Baños; Linda García-Hidalgo; Pedro Sobrevilla (Case Reports in Medicine)
Histone deacetylase (HDAC) inhibitors have shown significant activity in the treatment of cutaneous T-cell lymphomas (CTCL). The epigenetic alterations of CTCL not only are limited to altered histone acetylation but also include aberrant DNA gene methylation hence, the combination of an HDAC inhibitor with a DNA demethylating agent is a promising therapy to be tested. Here we report a mycosis fungoides patient having a dramatic response to hydralazine and valproate, two repositioned drugs as HDAC and DNA methylation inhibitors, respectively.